Photofunctionality in Porphyrin‐Hybridized Bis(dipyrrinato)zinc(II) Complex Micro‐ and Nanosheets. Issue 13 (27th February 2017) - Sakamoto, Ryota; Yagi, Toshiki; Hoshiko, Ken; Kusaka, Shinpei; Matsuoka, Ryota; Maeda, Hiroaki; Liu, Zheng; Liu, Qian; Wong, Wai‐Yeung; Nishihara, Hiroshi
Abstract: New bis(dipyrrinato)zinc(II) complex micro‐ and nanosheets containing zinc(II) porphyrin (N2 ) are synthesized. A liquid/liquid interface method between dipyrrin porphyrin ligand L2 and zinc acetate produces N2 with a large domain size. N2 can be layered quantitatively onto a flat substrate by a modified Langmuir–Schäfer method. N2 deposited on a SnO2 electrode functions as a photoanode for a photoelectric conversion system. The photoresponse of N2 covers the whole visible wavelength range (400–650 nm), with a maximum quantum efficiency of more than twice that of a bis(dipyrrinato)zinc(II) complex nanosheet without porphyrin. Abstract : Sheet lighting : A liquid/liquid interfacial synthesis gives bis(dipyrrinato)zinc(II) complex micro‐ or nanosheets containing porphyrin. The nanosheet deposited on a SnO2 electrode functions as a photoanode. The photoresponse covers the whole visible wavelength range (400–650 nm), with a maximum quantum efficiency greater than that of the nanosheet without porphyrin.